Penyelidikan Perilaku Interaksi Kimiawi Lapisan Diamond Film Pahat Karbida Pada Operasi Bubut Kering Bahan Al 6061 - Fransnazoan Sitorus (Jurnal Inotera, 2017)
The purpose of the research was to characterize diamond-film coating which is used as carbide tool coating material, especially coating material (diamond-film CVD) and substrate material (WC/Co) in general approach interaction of chemically, This is related to the research which reported about the functional failure of carbide tool coating material, used in dry machinery process of non-ferro metal in the initial wear. The study on the characteristics of tool diamond-film coating was conducted through chemical interaction approaches which occurred between the working object and tool through dry machining process. Cutting condition was v= 350 m/min; f= 0.15 mm/put; a= 1.5 mm in Initial-wear phase (tc= 1.736 min). The result of the test was abrasive wear VB = 0.070 mm. Chemical load was tested through micro analysis using energy dispersive analysis X-Ray spectroscopy (EDAX), the result of the test was the distribution of diamond-film coating elements in aluminum 6061 testing material on the cutting conditions indicated that diamond-film coating material was still significant. The conclusion of the study was that by using chemical interaction approaches, was no coating delamination in diamond-film coating of carbide tool. The phenomenon of the three approaches was the gradual disappearing of a part of the volume of diamond-film coating material which layered substrate material as the result of abrasive-coating wear.